La filosofia della cultura genesi e prospettive - Riccardo De Biase (Krinein: Studi Cassireriani, 2020)
This volume collects the contributions that scholars of the widest extraction, Italian and foreign, have dedicated to a fundamental theme for our times. The "culture"-object, a central theme of Cassirer's philosophy as well, is read, analyzed and proposed as a problematic node, but full of fruitful and current ideas, from multiple theoretical perspectives and diversified disciplinary fields.